Academic Backwardness among Students of Dhaka Medical College: A Retrospective Cohort Study - Hoque, Syeda Rumana; Sarker, Sujit Kumar; Akter, Mst Zobaida; Ahmed, Shehreen; Biswas, Palash Kumar; Chowdhury, Zakaria Mawla (The Journal of Ad-din Women’s Medical College, 2025)
Background: Socioeconomic challenges, inadequate early education, poor teaching quality, outdated curricula, insufficient infrastructure, limited technological access, and political instability influence academic backwardness among medical students in developing countries like Bangladesh. Financial constraints and family responsibilities hinder students' focus and resources. Educational systems often rely on learning and lack well-trained faculty and modern facilities. Additionally, language barriers and psychological stress further impact student performance. Efforts to address these issues include financial aid, teacher training, curriculum reforms, infrastructure improvements, and mental health support, all aimed at creating a supportive and effective learning environment. Objective: To evaluate the profile and sociodemographic characteristics in terms of students’ academic performance. Materials and Methods: A retrospective cohort study was conducted among students of Dhaka Medical College over six months (July 1, 2023 December 31, 2023). All undergraduate medical students in their 3rd, 4th, and 5th years at Dhaka Medical College who had lost at least one academic year were included in the study. The sample size was 46. Data were collected using a mixed questionnaire for appropriate statistical analysis. Results: Most respondents 36 (78.3%) were aged 2426, predominantly male 26 (56.5%), unmarried 38 (82.6%), and from nuclear families 44 (95.7%) with well-educated parents. Academic performance showed that only 5 (23.8%) passed the final exam on the first attempt. The range of academic year loss was 15 years. Key challenges included subject comprehension difficulties 15 (32.6%), pre-exam study habits 36 (78.3%), and nervousness during oral exams 42 (91.3%), along with familial issues like illness 20 (43.5%) and financial constraints 12 (26%). Conclusion: The study highlights that medical students from well-educated families face substantial academic and personal challenges, leading to significant delays in their education. This underscores the urgent need for support systems and focused interventions to address these issues effectively. The Journal of Ad-din Women's Medical College; Vol. 13 (1), Jan 2025; p 4-8